175k views
3 votes
I am keeping getting wrong answer and I don’t know why?

I am keeping getting wrong answer and I don’t know why?-example-1
User IMash
by
5.8k points

2 Answers

5 votes

Answer:

A.3a'2-2a+1

Explanation:

substitute a+1 for X so

3a'2 +3-2a-2

reorder and simplify

3a'2-2a+1

User DarrenRhodes
by
4.8k points
6 votes


\bf f(x)=3x^2-2x\qquad \qquad f(a+1)=3(a+1)^2-2(a+1) \\\\\\ f(a+1)=3(a^2+2a+1)-2a-2\implies f(a+1)=3a^2+6a+3-2a-2 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill f(a+1)=3a^2+4a+1~\hfill

User Ognyan Dimitrov
by
5.0k points